Geometric modeling of 3D woven preforms in composite T-joints - Yan, Shibo; Zeng, Xuesen; Brown, Louise; Long, Andrew (SAGE Publications, 2017)
A common method to fabricate net-shaped three-dimensional (3D) woven preforms for composite T-joints is to weave flat 3D preforms via a standard weaving machine with variation in binder yarn path and then separate the preform in the form of a bifurcation. Folding introduces fiber architecture deformation at the 3D woven bifurcation area. In this paper, a geometric modeling approach is proposed to represent the realistic fiber architecture, as a preprocessor for finite element analyses to predict composite structural performance. Supported by X-ray micro-computed tomography (mCT), three important deformation mechanisms are observed including yarn stack shifting, cross-section bending, and cross-section flattening resulting from the folding process. Furthermore, a set of mathematical formulae for simulation of the deformations in the junction region are developed and satisfactory agreement is observed when compared with mCT scan results.